Effects of Yellow-Tinted Lenses on Visual Attributes Related to Sports Activities and Daily Life in Late Middle-aged Adults - Kazuhiro Aoki; Yoshimitsu Kohmura; Shigeki Murakami; Yuki Someya (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The purpose of this study was to clarify the effects of colored lenses on the visual performance of middle-aged people. The subjects were 19 middle-aged people with a mean age of 57.4 ±6.0 years. Five different functional lenses were used in the experiments: colorless lenses and four colored lenses (Light-yellow, Dark-yellow, Light-gray, and Dark-gray). Using each lens type, contrast sensitivity, depth perception, hand–eye coordination, dynamic visual acuity, and visual acuity/low-contrast visual acuity were measured. Visual acuity/low-contrast visual acuity was measured under the four conditions of Evening, Evening + Glare, Day, and Day + Glare. Results showed that dynamic visual acuity and depth perception did not differ among the lens types, but hand–eye coordination measurements had a significantly shorter time with the Light-yellow and Dark-yellow lenses than the Dark-gray lenses. Low-contrast visual acuity under Evening and Evening + Glare conditions tended to be lower with the Dark lenses than the Colorless and Light-yellow lenses. The subjects rated the Yellow lenses as bright in a subjective questionnaire evaluation.